Law as a leap of faith and other essays on law in general - Gardner, John, 1965- (Oxford : Oxford University Press, 2012)
In a series of essays, John Gardner has developed distinctive and engaging answers to the central questions of legal philosophy, cutting through the technicalities of the subject to clarify and reinvigorate the main arguments about the nature of law.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Law -- Philosophy; Jurisprudence